Critical issues in preparing effective early childhood special education teachers for the 21st century classroom : interdisciplinary perspectives - Rotatori, Anthony F.; Obiakor, Festus E. (Contemporary perspectives in special education., 2016)
The purpose of this book is to provide a forum for an interdisciplinary scholarly dialogue with regard to preparing teachers for early childhood special education. In addition, it is aimed at examining and making available relevant and most recent scholarship to practitioners and at addressing critical issues and perspectives around preparing effective educators for the 21 century classroom and the future. This book intends to illuminate a complex and challenging task of preparing effective educators through the lenses of several educational disciplines, including but not limited to, teacher education, general education, special education, early childhood education, and urban education.The information in this work will focus on several educational disciplines that have the most immediate implications for teacher preparation and practice. The overall educational knowledge base will be enhanced due to the educational interdisciplinary approach. This has additional implications for teacher education, special education, educational leadership, curriculum and instruction, educational policy, and urban education, to name a few. The multidimensional nature of the book gives it the freedom to highlight multiple and diverse voices while at the same time providing a forum for different (and sometimes divergent) methodologies, philosophies, and ideologies.